Drivers of Option Liquidity: Evidence from India - Sanjay Sehgal; Vijaykumar N (Journal of Accounting, Business and Management (JABM), 2008)
The financial derivatives market in India has a more recent origin compared to the stock market. In this paper we investigate the relationship between the stock market characteristics and option market liquidity using daily data for equity options and underlying stocks in the Indian context. We find that while option liquidity proxies (options contract volume in terms of numbers and rupee value) are positively related with stock price, stock liquidity and stock return volatility; it is inversely related to uncertainty in the information environment measured by company size. We also find evidence for day of the month effect for at least one year of the study. We get consistent results with both the measures of option liquidity (options contract volume in terms of numbers and rupee value) as well as for different option types (call and put options). The findings are in the conformity with those for developed markets and shall be useful for institutional investors who actively trade in the options market owing to lower transaction cost, leverage advantage and short sale restrictions on the underlying stocks.